The Scientific and Clinical Case for Reviewing Diagnostic Radiopharmaceutical Extravasation Long-Standing Assumptions - Osborne, Dustin; Lattanze, Ronald; Knowland, Josh; Bryant, Tonia E.; Barvi, Iryna; Fu, Yitong; Kiser, Jackson W. (Frontiers in Medicine, 2021)
Background: The patient benefit from a diagnostic nuclear medicine procedure far outweighs the associated radiation risk. This benefit/risk ratio assumes a properly administered radiopharmaceutical. However, a significant diagnostic radiopharmaceutical extravasation can confound the procedure in many ways. We identified three current extravasation hypotheses espoused by medical societies, advisory committees, and hundreds of individual members of the nuclear medicine community: diagnostic extravasations do not cause harm, do not result in high absorbed dose to tissue, and require complex dosimetry methods that are not readily available in nuclear medicine centers. We tested these hypotheses against a framework of current knowledge, recent developments, and original research. We conducted a literature review, searched regulatory databases, examined five clinical cases of extravasated patients, and performed dosimetry on those extravasations to test these globally accepted hypotheses. Results: A literature review found 58 peer-reviewed documents suggesting patient harm. Adverse event/vigilance report database reviews for extravasations were conducted and revealed 38 adverse events which listed diagnostic radiopharmaceutical extravasation as a factor, despite a regulatory exemption for required reporting. In our own case material, assessment of care was evaluated for five extravasated patients who underwent repeat imaging. Findings reflected results of literature review and included mis- or non-identification of lesions, underestimation of Standardized Uptake Values (SUVs) by 19–73%, classification of scans as non-diagnostic, and the need to repeat imaging with the associated additional radiation exposure, inconvenience, or delays in care. Dosimetry was performed for the same five cases of diagnostic radiopharmaceutical extravasation. Absorbed doses to 5 cm3 of tissue were between 1.1 and 8.7 Gy, and shallow dose equivalent for 10 cm2 of skin was as high as 4.2 Sv. Conclusions: Our findings suggest that significant extravasations can or have caused patient harm and can irradiate patients' tissue with doses that exceed medical event reporting limits and deterministic effect thresholds. Therefore, diagnostic radiopharmaceutical injections should be monitored, and dosimetry of extravasated tissue should be performed in certain cases where thresholds are thought to have been exceeded. Process improvement efforts should be implemented to reduce the frequency of extravasation in nuclear medicine.